Criminal lifestyle, psychopathy and prison adjustment among female inmates - Pinheiro, Marina (2022)
Several studies have sought the factors that are related to prison adjustment. However, this construct is poorly explored among female populations and even less so in those with characteristics of psychopathy. Thus, the present study aims to understand prison adjustment among female offenders and determine the role of psychopathy and criminal lifestyle in predicting it. Both institutional infractions and health care utilization were used as indicators of prison adjustment. A sample of 63 female offenders was assessed with the Psychopathy Checklist-Revised (PCL-R) and the Lifestyle Criminality Screening Form-Revised (LSCF-R). 88.9% of female offenders search for health care services, and 67.2% had at least one institutional infraction. Negative binomial regressions revealed that PCL-R total scores, LSCF-R total scores, and drug abuse were predictors of institutional infractions. None of the assessed variables are statistically associated with health care services utilization. These results are of particular importance for psychologists and correctional managers, given the interest in reducing the risk of maladjustment and increase the process of adaptation to prison.